Inhibitory effect of pentoxifylline on the synthesis and deposition of glycosaminoglycans in hypothyroid skin. Issue 1 (31st December 2022) - Bocheva, Georgeta; Malinova, Lina; Bakalov, Dimitar; Bogdanov, Georgi; Hristova, Julieta; Svinarov, Dobrin
Abstract: The skin manifestations in hypothyroidism are common but their advanced forms do not have adequate therapy. Along with achievement of euthyroidism, thyroid-associated dermatopathy (TAD) needs an inhibition of the proliferation and activation of fibroblasts, and of the glycosaminoglycans synthesis. Pentoxifylline (PTX) exerts multifaceted effects and has shown properties to inhibit certain constitutive activities of dermal fibroblasts. The aim of this study was to determine the histopathological changes and to establish the amount and distribution of mucin in hypothyroid skin, with or without treatment with PTX. Hypothyroid skin showed abundant diffuse mucin deposition in all dermal compartments in comparison with euthyroid skin. After administration of PTX in dose 100 mg/kg daily, there was a significant decreased amount of mucin in the dermis. The improvement of the dermal histological manifestations, in general demonstrated by narrowing between the dermal collagen fibers and by a decrease in mucin deposition, might be explained with dose-dependent PTX inhibition of the synthesis and accumulation of glycosaminoglycans. The histological results of this study confirmed several clinical observations about the beneficial effect of PTX on clinical skin manifestations in hypothyroid state. Therefore, we may propose PTX as a new potential therapeutic agent for TAD treatment. Further studies are needed to fully establish the effect of PTX on dermal fibroblasts after continuous administration.